2017
DOI: 10.1021/acs.biomac.7b00877
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Cellular Organelles by Fluorescent Plasmid DNA Nanoparticles

Abstract: The development of a suitable delivery system and the targeting of intracellular organelles are both essential for the success of drug and gene therapies. The conception of fluorescent ligands, displaying targeting specificity together with low toxicity, is an emerging and reliable tool to develop innovative delivery systems. Biocompatible BSA or pDNA/ligand nanoparticles were synthesized by a coprecipitation method and were shown to display adequate sizes and morphology for delivery purposes, and positive sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In fact, the results mentioned above have suggested that the mcDNA-p53 vector is effective in decreasing cancer cell viability, which can be associated with this repression of cell proliferation. This growth inhibitory effect was also found in a similar assay performed by Costa et al, after transfection with a pDNA vector encoding the p53 gene [28]. Thus, it can be concluded that overexpression of p53 protein by mcDNA can lead to the reinstatement of p53 functions, which was once affected by E6 degradation mechanisms.…”
Section: Discussionsupporting
confidence: 71%
“…In fact, the results mentioned above have suggested that the mcDNA-p53 vector is effective in decreasing cancer cell viability, which can be associated with this repression of cell proliferation. This growth inhibitory effect was also found in a similar assay performed by Costa et al, after transfection with a pDNA vector encoding the p53 gene [28]. Thus, it can be concluded that overexpression of p53 protein by mcDNA can lead to the reinstatement of p53 functions, which was once affected by E6 degradation mechanisms.…”
Section: Discussionsupporting
confidence: 71%
“…In the last decades, considerable advances have been made in the conception of nucleic acid-based delivery systems to overcome the major drawbacks of payload delivery to eukaryotic cells, namely, cellular uptake/internalization, endosomal escape, targeting a specific subcellular compartment, and ultimately, the induction of therapeutic action [19,[21][22][23][24]. In line with this aim, micelles, polymers, lipid-and peptide-based nanoparticles are among the most studied systems for gene release [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the affinity of the systems for mitochondria, after cellular transfection, mitochondria were separated from the cytosolic fraction, verifying greater accumulation of nanoparticles in isolated mitochondria compared to the cytosol fraction, through quantification of rhodamine fluorescence [ 145 ]. Costa et al also created calcium carbonate delivery systems capable of encapsulating p53 and ND1-GFP plasmids [ 146 ]. The nanoparticles formulated with the compound [16]phenN 2 showed an affinity for mitochondria.…”
Section: Nanotechnology In Mitochondrial Gene Therapymentioning
confidence: 99%
“…The fluorescence of [16]phenN 2 in isolated mitochondria was quite high when compared to the fluorescence of this compound in the cytosol or in lysosomes, where fluorescence was residual. Mitochondrial targeting of systems with [16]phenN 2 was further reinforced when plasmids were replaced by BSA, which resulted in an accumulation of BSA within the mitochondria of cells transfected with these nanoparticles, while this accumulation did not occur in the cytosol and the lysosome [ 146 ].…”
Section: Nanotechnology In Mitochondrial Gene Therapymentioning
confidence: 99%